Specific identification of toads and frogs based on the mouthpart configuration of their tadpoles (Journal of Science and Technology, 2016)
The mouth part configuration of the tadpoles of some anuran amphibians were examined using a dissecting microscope. Features examined included the tooth rows, oral disc, and the jaw sheath. Two different groups of tadpoles were collected and suitable pond conditions provided for them tometamorphose into adults. One group metamorphosed to Bufo regularis and the other to Hyperolius nasatus. The Bufo regularis tadpoles had a jaw sheath that was serrate and valley-sawed with a Labial Tooth row Formula (LTF) of 2(2)/3. The Hyperolius nasatus tadpoles on the other hand had ajaw sheath that was cuspate pointed with a Labial Tooth row Formula of 2(2)(3)/3(3). The findings from this study show that it is possible to identify frogs and toads from their tadpoles without having to look for the breeding adults in the wild.